-7(6n+2)=3n-7(6n+8)

Simple and best practice solution for -7(6n+2)=3n-7(6n+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6n+2)=3n-7(6n+8) equation:



-7(6n+2)=3n-7(6n+8)
We move all terms to the left:
-7(6n+2)-(3n-7(6n+8))=0
We multiply parentheses
-42n-(3n-7(6n+8))-14=0
We calculate terms in parentheses: -(3n-7(6n+8)), so:
3n-7(6n+8)
We multiply parentheses
3n-42n-56
We add all the numbers together, and all the variables
-39n-56
Back to the equation:
-(-39n-56)
We get rid of parentheses
-42n+39n+56-14=0
We add all the numbers together, and all the variables
-3n+42=0
We move all terms containing n to the left, all other terms to the right
-3n=-42
n=-42/-3
n=+14

See similar equations:

| 2r²+10r-8=0 | | 3(z+17)=75 | | 35-8j=3 | | 2y2+14y=−20 | | x/28=(4-x)/4 | | 3h+9=-11+8h | | 1x+2/3=2x-2 | | 3y+2=14+y | | 27-5t=7 | | =3y+14 | | x=1/7x7/2 | | 12-4c=0 | | 2(y-1)-5=-3(-8y+3)-4y | | 1+8u=17 | | 2(x+3.80)=22.80 | | 40=7h+5 | | 2x+7=73 | | 2(y-1)-5=-3(-8+3)-4y | | 32=4+7w | | 16/8=(x-4) | | -12(-2x-4)=-72 | | Y=x2+4x+4 | | 3(w-9)=-9w-15 | | 9x-1=23 | | 5y-8-3y=12 | | 3x/4-10=17 | | 17/3=x-7/3 | | -2(10x+8)=-24 | | -15=3(r-9) | | -8v+6(v-6)=-24 | | a+28.6=43 | | a/16=6.8 |

Equations solver categories